Cartilage Stiffness Effect on Foot Biomechanics of Chinese Bound Foot: A Finite Element Analysis - Zhang, Yan; Awrejcewicz, Jan; Baker, Julien S.; Gu, Yaodong (Frontiers in Physiology, 2018)
The purpose of this study is to investigate the effect of cartilage stiffness on inner foot biomechanics of Chinese bound foot while weight bearing using finite element method. A three-dimensional FE model of bound foot involving 28 bones, 72 ligaments, 5 plantar fascia, cartilages, and encapsulated soft tissue was constructed and validated. To conduct the sensitivity analysis of cartilage stiffness, the incremental Young’s modulus of 1MPa, 5MPa, 10MPa, and 15MPa were assigned to the cartilage. 25% of the body weight was applied to the Achilles tendon to adjust the anterior- posterior displacement of center of pressure agreeable with the measured result. As the Young’s modulus of cartilage increased, the peak von Mises stress in the fifth metatarsal increased obviously, while that in the calcaneus remains unchanged. The plantar fascia experienced reduced total tension with stiffer cartilage. The cartilage stiffening also caused a general increase of contact pressure at mid- and forefoot joints. Cartilage stiffening due to foot binding increased risks of foot pain and damage of longitude arch. Knowledge of this study is of great significance in understanding biomechanical behavior of bound foot and contributes to enhancing the comprehension of functional adaptions in foot binding.